Deoxyribonucleic Acid Relatedness of Enterococcus hirae and “Streptococcus durans” Homology Group II - KNIGHT, ROYCE G.; SHLAES, DAVID M. (International Journal of Systematic and Evolutionary Microbiology, 1986)
Enterococcus hirae and “Streptococcus durans” homology group II were found to be highly related by using deoxyribonucleic acid-deoxyribonucleic acid hybridization and well-characterized strains. The “S. durans” homology group II strains used in this study were from cattle feces and human sputum. Therefore, we conclude the “S. durans” (homology group II) belongs to the same taxon as E. hirae and that the habitat of this species includes human and cattle sources.